Predisposing and Enabling Factors Relationship with Successful Treatment of Pulmonary Tuberculosis (TB) - Rafiah Maharani Pulungan; Putri Permatasari (Jurnal Kesehatan Prima, 2021)
The increase in pulmonary TB cases is related to the success of treatment. Rough treatment will lead to multi-drug resistant TB (MDR TB). The purpose of this study was to analyze the relationship of Predisposing, and enabling factors with the successful treatment of pulmonary TB in the Cikulur Community Health Center, Lebak Regency. This study used a Case-control research design. The sampling technique was purposive sampling, and a sample size of 82 people. The independent variables were predisposing factors (age, gender, education level, employment status, motivation, knowledge and attitudes), enabling factors (medication adherence, drug side effects, and access to health facilities). The dependent variable was the success of TB treatment. Data analysis using Chi-Square test and multiple logistic regression. The results showed that a person with pulmonary TB with non-working status, adherence to treatment, and access to health facilities was 5.002 times easy to succeed in TB treatment. The factors most related to the success of treatment were occupational status, medication adherence and access to health facilities. It is suggested that health services need to increase the accessibility of TB patients in the fulfillment of treatment so that patients can improve their success in recovery in therapy. Also, sufferers take medication regularly and according to the recommendations for success of treatment